(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article discusses the significance of reading for pleasure in order to acquire vocabulary. It also discusses how children pick up new words when they are explicitly taught them, as well as how they pick up new terms accidentally through extensive reading and other language-rich activities. Certain terms can be thoroughly taught to kids, giving them the knowledge, they require to understand what they read. For the purpose of expanding their vocabulary, students who do not read independently must receive this direct instruction